(untitled) (Asian Journal of Medical and Biological Research, 2020)
This study was aimed to isolate and identify the potential probiotic bacteria from broiler chickens and their related environment of the two districts in Bangladesh by using cultural and biochemical techniques and detection of the selected isolated probiotic potential bacterial species by using polymerase chain reaction (PCR). In this context five probiotic bacteria species of five bacteria genera were screened out from 750 samples in where there were 186 Lactobacillus genus isolates, 102 Bacillus genus isolates, 112 Streptococcus genus isolates, 220 Enterococcus genus isolates and 33 Bifidobacteriumgenus isolates on the basis of biochemical properties like 10% solution of total 22 different sugars. Other biochemical tests like MR-VP, Oxidase, Catalase, Citrate utilization, MIU and Indole test were major. Genus was detected through specific genus target gene and 16S r DNA based PCR. Selected probiotic bacteria species were detected through species specific target gene PCR. We confirmed 23 Lactobacillus acidophilus species isolates, 14 Bacillus subtilisisolates, 19 Streptococcus thermophilusisolates, 31 Enterococcus faeciumisolates and 09 Bifidobacteriumbifidumisolates at species level with ddlgene, apr-E gene, 16S-23S ITS gene, BIBI gene, Stp-TH gene primers. The novelty of this study is at first time in Bangladesh, we isolated and identified five selected potential probiotic species from the gastro-intestinal tract of broiler chickens and their related environmental sources by not only using traditional cultural, biochemical techniques but also genus and species specific target gene based PCR. Asian J. Med. Biol. Res. September 2020, 6(3): 383-399